Perbedaan Karakteristik Kotoran Cacing Tanah dari Lahan Sayuran Organik dan Konvensional di Kecamatan Baturiti - BINTANG PURNIASARI; I WAYAN DANA ATMAJA; NI NENGAH SONIARI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Characteristics Differences of Casting from Organic and Conventional Vegetables Field in Baturiti District Casting is solid waste released from the anus of earthworms, containing organic matter, and microorganisme that can provide nutrients in the soil so they can be directly absorbed by plants. This study discusses the characteristic differences of casting seen from the physical, chemical and biological properties of organic vegetable field and conventional vegetable field in Baturiti District. The research was conducted from October 2018 to April 2019. The study including in deciding the location, taking samples of earthworms with soil, acclimatization process for earthworms, and analysis of physical, chemical, and biological properties of casting. The results of physical analysis of casting in organic and conventional farms have the same texture, the sandy clay loam textures. The results of chemical analysis of casting showed pH, N-total, Amonium, Nitrate and P-available were higher in organic field than conventional field. The pH value in organic soil is 6,58 and conventional soil is 6,50; N-total in organic soil is 0,75% and conventional soil is 0,65%; amonium and nitrate in organic soils is 6,44% and 2,1% compared to conventional field 4,35% and 1,92%, and P-available on organic field 393,40 mg kg-1 and conventional field 130,22 mg kg-1. The results of biological analysis of bacteria and fungi shows higher value in organic field than conventional field. The population of bacteria and fungi in organic field was 20,35 x 108 spk g-1 of casting and 4,44 x 105 spk g-1 of casting whereas in conventional field 10,20 x 108 spk g-1 of casting and 2,99 x 105 spk g-1 of casting.